Analisis Kualitas Website UMKM Nasional Menggunakan Metode Heuristic Evaluation dan Google Lighthouse - Apriyanto Alhamad; Sudirman Melangi; Maryam Hasan; Sitti Nur Avifa Olii; Warid Yunus; Hastuti Dalai (Jurnal Minfo Polgan, 2026)
This study analyzes the quality of SMEsta, a national MSME digital portal, by combining user-based Heuristic Evaluation and Google Lighthouse auditing. The background of the study is the strategic role of public websites in supporting MSME digitalization and the need to evaluate not only interface convenience but also technical readiness on mobile access. The objective is to describe SMEsta usability, identify technical quality gaps, and formulate improvement priorities from both sources of evidence. The research used a quantitative descriptive case-study approach. Users evaluated three pages, namely Home, Export MSME Recommendations, and FAQ, through a Likert questionnaire mapped to Nielsen's ten heuristics, while the same pages were audited through Google Lighthouse mobile configuration. The instrument was validated by experts and showed reliable internal consistency with Cronbach's alpha of 0.910. From 105 responses, 100 valid responses were analyzed. The findings show that SMEsta usability is in the high category, with an overall mean of 4.19 and an index of 79.80. Error prevention obtained the highest mean of 4.32, whereas help users recognize, diagnose, and recover from errors was the lowest with a mean of 3.73. Lighthouse results indicate uneven technical quality, especially performance: the Export MSME Recommendations page scored 56, the Home page scored 36, and the FAQ page scored 23, while SEO reached 100 on all pages. The study concludes that SMEsta is generally usable, but performance optimization and clearer contextual error support should become priority improvements